Effectiveness Of Implementation Of Corporate Social Responsibility (CSR) In The Environmental Law Enforcement - Irwansyah Irwansyah; Gianto Gianto; Andi Syahwia (Pattimura Law Journal, 2016)
Development in Indonesia refers to the concept of sustainable development (sustainable development) and responsibility for the environment . Companies have a social responsibility to social and environmental consequences of environmental damage that caused . Implementation of corporate social responsibility (Cooperate Social Responsibility) is an important part in the framework part of the enforcement of environmental law . Implementation of CSR growing rapidly , including in Indonesia . Through Law No. 40 Year 2007 regarding Limited Liability Company , specifically in Article 74, in response to the action of the business world to social and environmental causes damages to society . But in application / CSR implementation will be undertaken by the company is not maximized with implications for the enforcement of environmental law.